A prospective study on abnormal uterine bleeding with sonological and histopathological correlation in women attending tertiary care hospital - Prabhudev, Prema; I. S., Sapna; Pujar, Tejaswi V.; K. P., Achala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abnormal uterine bleeding (AUB) is a common problem among women in the reproductive age group, with reported prevalence in India being 17.9%, AUB has a substantial effect on health-related quality of life and morbidity related if requiring surgeries. The objective of this study was to evaluate various histopathological features in endometrial curetting and co-relate them with transvaginal ultrasonographic findings. Methods: The study consisted of 500 cases who presented to the Department of Obstetrics and Gynaecology with complaints of abnormal uterine bleeding. Relevant history was elicited from all cases and a clinical examination was done. All cases underwent endometrial biopsy followed by transvaginal ultrasonography before surgery and the results were compared with the histopathological study of the specimen. Results: 16.7% of patients diagnosed with AUB had severe anemia requiring transfusion of blood. 4.2% of subjects in the study were nulliparous. 59.7% of subjects had an endometrial thickness ranging from 10mm to 14.9 mm in the transvaginal ultrasonographic study. Endometrial carcinoma accounted for 1.4% of the study population. Normal USG findings were seen in 18.1% of patients. Conclusions: In conclusion, a significant association was found between ultrasound and histopathological findings.